Her story : women in Christian tradition - MacHaffie, Barbara J., 1949- (Fortress Press, 2006)
An accessible, introductory text first published by Fortress Press in 1983, Her Story: Women in Christian History has sold over 30,000 copies of the first edition and has ably helped readers recover the oft-ignored or submerged stories of women in the Christian tradition, from biblical times to now.Barbara MacHaffie, who wrote the brief history and compiled a lively anthology of companion primary readings, has revised and updated the text and readings. In this new edition, history and primary readings are combined and augmented with helpful pedagogical tools.This new textbook, which offers sympathetic coverage of all Christian traditions, is supported by a dedicated companion website that includes chapter summaries, questions for discussion and web links that vividly bring the stories of women to life in portraits, artifacts, and other primary materials.